Electronic Archive Management in an Effort to Improve Service Quality at IAIN Palangka Raya - Puspita, Puspita (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2024)
The development of internet technology in Indonesia is entering the digital era which greatly affects the community to fulfill information needs through archives in electronic form. This study aims to review the management of electronic archives in improving the quality of service at IAIN Palangka Raya as one of the best archive units in Central Kalimantan. The analysis of electronic archive management in improving service quality is reviewed through the dimensions of tangible, responsive, assurance, reliability, and empathy. This study uses a qualitative descriptive method with data collection techniques carried out by triangulation with primary and secondary data sources. Data collection methods were obtained through questionnaires, interviews, and documentation by testing data sources through checking data from sources that were obtained repeatedly. In analyzing the data, the researcher used data collection, data reduction, data display, and conclusion drawing. The results of the study as a whole explain that the application of electronic archive management has been proven to improve service quality through tangible, responsive, assurance, reliability, and empathy dimensions at the archives unit of IAIN Palangka Raya. This condition is due to the quality of user services to the archive access service management system at IAIN Palangka Raya based on the percentage shown is satisfied. However, the electronic archive service quality management system at IAIN Palangka Raya still needs to be completed and improved because some services are still manual and not standardized for archive management from ANRI.